Nanotechnology Applications in Sepsis: Essential Knowledge for Clinicians - Inês Vasconcelos; Tiago Santos (MDPI AG, 2023)
Sepsis is a life-threatening condition caused by a dysregulated host response to an invading pathogen such as multidrug-resistant bacteria. Despite recent advancements, sepsis is a leading cause of morbidity and mortality, resulting in a significant global impact and burden. This condition affects all age groups, with clinical outcomes mainly depending on a timely diagnosis and appropriate early therapeutic intervention. Because of the unique features of nanosized systems, there is a growing interest in developing and designing novel solutions. Nanoscale-engineered materials allow a targeted and controlled release of bioactive agents, resulting in improved efficacy with minimal side effects. Additionally, nanoparticle-based sensors provide a quicker and more reliable alternative to conventional diagnostic methods for identifying infection and organ dysfunction. Despite recent advancements, fundamental nanotechnology principles are often presented in technical formats that presuppose advanced chemistry, physics, and engineering knowledge. Consequently, clinicians may not grasp the underlying science, hindering interdisciplinary collaborations and successful translation from bench to bedside. In this review, we abridge some of the most recent and most promising nanotechnology-based solutions for sepsis diagnosis and management using an intelligible format to stimulate a seamless collaboration between engineers, scientists, and clinicians.